Wear particle classifier system based on an artificial neural network - Gonçalves, Valdeci Donizete [UNESP]; De Almeida, Luis Fernando; Mathias, Mauro Hugo [UNESP] (My University, 2010)
This paper describes a method to identify morphological attributes that classify wear particles in relation to the wear process from which they originate and permit the automatic identification without human expertise. The method is based on the use of Multi Layer Perceptron (MLP) for analysis of specific types of microscopic wear particles. The classification of the wear particles was performed according to their morphological attributes of size and aspect ratio, among others. © 2010 Journal of Mechanical Engineering.
Keywords: Artificial neural network; Expert system; Wear particles analysis